2004
DOI: 10.1097/01.fpc.0000114747.08559.49
|View full text |Cite
|
Sign up to set email alerts
|

CYP3A5*1-carrying graft liver reduces the concentration/oral dose ratio of tacrolimus in recipients of living-donor liver transplantation

Abstract: These results indicate that in recipients of LDLT, the pharmacokinetics of tacrolimus is influenced by flux via P-glycoprotein in the intestine during the first week; after that, it is mostly the hepatic metabolism that contributes to the excretion of tacrolimus, and carriers of the CYP3A5*1/*1 genotype require a high dose of tacrolimus to achieve the target concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
131
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(155 citation statements)
references
References 31 publications
21
131
3
Order By: Relevance
“…This could be due to the higher rates of metabolism in CYP3A5 expressors and thus, the dose required to achieve target concentration in patients with donor genotype CYP3A5 expressors was higher than non-expressors. Our finding was consistent with results from other studies [5,6,9]. However, similar impact on C0/D ratio was not demonstrated in patients with donor ABCB1 variant alleles.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This could be due to the higher rates of metabolism in CYP3A5 expressors and thus, the dose required to achieve target concentration in patients with donor genotype CYP3A5 expressors was higher than non-expressors. Our finding was consistent with results from other studies [5,6,9]. However, similar impact on C0/D ratio was not demonstrated in patients with donor ABCB1 variant alleles.…”
Section: Discussionsupporting
confidence: 83%
“…It would be of clinical interest to understand changes in pharmacokinetic parameters in relation to gene polymorphisms in an Asian population. Although some studies have been conducted in China, Japan and Korean liver transplant populations [4][5][6]9], as well as Singapore and Korean renal transplant populations [8][9], the influence of both donor and recipient gene polymorphisms on the pharmacokinetics of tacrolimus remains to be clearly defined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we showed that the cytochrome P450 (CYP) CYP3A5*1 allele not only in the liver (donor genotype) but also in the small intestine (recipient genotype) achieved lower concentration/dose (C/D) ratio of tacrolimus than that with CYP3A5*3 (rs776746)/*3 homozygotes in living-donor liver transplant patients. [3][4][5][6] Recently, a new SNP in the CYP3A4 gene, CYP3A4*1G in intron 10, has been found in human lymphoblastoid cell lines from different ethnic groups and is the most common SNP in Japanese patients. 7,8) Miura et al 9) reported that dose-adjusted area under the concentration-time curve and trough level of tacrolimus in renal transplant patients with CYP3A4*1G/*1G was lower than those in patients with CYP3A4*1/*1.…”
Section: Influence Of Cytochrome P450 (Cyp)mentioning
confidence: 99%
“…Goto et al (2004) indicated that the pharmacokinetics of tacrolimus are influenced by the graft CYP3A5 genotype. Yet another study revealed that patients with a liver graft with the CYP3A5*1 allele had a lower C/D ratio of tacrolimus than patients with a liver graft with the CYP3A5*3/*3 genotype (Rahsaz et al, 2012).…”
Section: Discussionmentioning
confidence: 99%